Efektivitas Dua Jenis Mulsa terhadap Tingkat Serangan Hama Pelipat Daun (Brachmia Convolvuli Wals.) - Ardiansyah Ardiansyah; Bambang Supeno; Wahyu Astiko (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Sweet potato (Ipomoea batatas L.) is a strategic food commodity that has the potential as an alternative carbohydrate source and functional food. However, its productivity is still hampered by attacks by plant pests (OPT), one of which is the leaf-folding pest (Brachmia convolvuli). This study aims to determine the effectiveness of two types of mulch on the population and intensity of leaf-folding pest attacks on purple sweet potato plants. The research method used is experimental. The experimental design is (RAK) Randomized Block Design, with 3 treatment. The treatment are N0 control (no treatment), N1 black silver plastic mulch and N2 straw mulch, each experimental unit was repeated 9 times and obtained 27 treatment units. Data were analyzed using analysis of variance (ANOVA) at a significance level of 5% followed by the Honestly Significant Difference (HSD) test at the same level. The result showed that the type of mulch significantly affected the pest population and attack intensity. Straw mulch gave significant results, with a population of 9,96 individuals and an attack intensity of 19.09%. So it is more effective in suppressing the development and attack of leaf folding pests compared to other treatments.